Effect of spacing and fertilizer management on the yield and yield attributes of mukhikachu (Colocasia esculenta Schott.) (Bangladesh Journal of Agricultural Research, 2016)
Field experiments were carried out in the Agronomy field of BARI, Joydebpur, RARS, Jamalpur and RARS, Ishurdi during two consecutive kharif seasons of 2012 and 2013 to determine the suitable plant spacing and optimum fertilizer dose for higher yield of mukhikachu. Three levels of spacing viz., 60 cm x 60 cm, 60 cm x 45 cm and 60 cm x 30 cm and three levels of fertilizer dose viz., recommended dose (3000-96-27-81-18 kg ha-1 of CD-N-P-K-S), 25% less than the recommended dose and 25% higher than the recommended dose were used as treatment variables. The experiments were laid out in factorial randomized complete block design with three replications. Results revealed that the closer spacing (60 cm x 30 cm) in combination with 25% higher than the recommended fertilizer dose gave the maximum edible yield of mukhikachu (two years average) at all locations (20.04 t ha-1, 20.75 t ha-1 and 16.63 t ha-1 at Joydebpur, Jamalpur and Ishurdi, respectively). The wider spacing (60 cm x 60 cm) coupled with 25% less than the recommended fertilizer dose produced the lowest yield (two years average). The maximum benefit- cost ratio (two years average) was obtained from the combination of the recommended fertilizer dose and 60 cm x 30 cm spacing, that were 2.93 at Joydebpur and 3.42 at Ishurdi, while at Jamalpur the maximum benefit-cost ratio (two years average) was found maximum from 60 cm x 30 cm spacing with 25% higher than the recommended fertilizer dose (3.12).Bangladesh J. Agril. Res. 41(4): 713-723, December 2016